2021
DOI: 10.3389/fgene.2021.582357
|View full text |Cite
|
Sign up to set email alerts
|

Combined Low-/High-Density Modern and Ancient Genome-Wide Data Document Genomic Admixture History of High-Altitude East Asians

Abstract: The Tibetan Plateau (TP) is considered to be one of the last terrestrial environments conquered by the anatomically modern human. Understanding of the genetic background of highland Tibetans plays a pivotal role in archeology, anthropology, genetics, and forensic investigations. Here, we genotyped 22 forensic genetic markers in 1,089 Tibetans residing in Nagqu Prefecture and collected 1,233,013 single nucleotide polymorphisms (SNPs) in the highland East Asians (Sherpa and Tibetan) from the Simons Genome Divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 53 publications
(53 reference statements)
2
20
0
Order By: Relevance
“…Genetic similarity and continuity between the Sherpas and ancient populations and Tibetan groups on the Tibetan Plateau were further confirmed by their excess shared alleles revealed in f-statistics, qpWave/qpAdm-based admixture models, and qpGraph-based evolutionary topology. Moreover, we found that Lajia_LN-related ancestry contributed the most to the gene pool of modern Sherpa and Tibetan populations, suggesting that Neolithic millet farmers played a pivotal role in the formation of modern Sherpas and Tibetans, which was consistent with previous genetic findings [36,53,59]. The haplotype-based genetic observations further confirmed the recent common ancestor sharing between the Sherpas and Tibetans.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Genetic similarity and continuity between the Sherpas and ancient populations and Tibetan groups on the Tibetan Plateau were further confirmed by their excess shared alleles revealed in f-statistics, qpWave/qpAdm-based admixture models, and qpGraph-based evolutionary topology. Moreover, we found that Lajia_LN-related ancestry contributed the most to the gene pool of modern Sherpa and Tibetan populations, suggesting that Neolithic millet farmers played a pivotal role in the formation of modern Sherpas and Tibetans, which was consistent with previous genetic findings [36,53,59]. The haplotype-based genetic observations further confirmed the recent common ancestor sharing between the Sherpas and Tibetans.…”
Section: Discussionsupporting
confidence: 91%
“…The previous genetic analyses focused on the peopling of Tibetan Plateau mainly based on allele-based sharing ancestry or only modern genomes without the comprehensively comparative analysis based on both modern and ancient references [9, 57,58]. Our recent population genetic analyses have started to directly explore the direct genetic contribution from ancient East Asians to modern Tibetan Plateau Tibetans based on ancient genomes, but the genetic history of Sherpa people and their forensic characteristics still need to be further studied [59][60][61]. In the present study, we first performed an InDel-based forensic and population genetic study to explore the genetic relatedness between Sherpa highlanders and worldwide reference populations.…”
Section: Discussionmentioning
confidence: 99%
“…Southwestern East Asia is one of the most ethnolinguistically diverse regions around the world. Genetic origin, subsequent migration, isolation, plausible admixture, and local adaptation history of ethnolinguistic southern Chinese populations were widely discussed via different genetic markers, mainly including autosomal short tandem repeats (STRs), single nucleotide polymorphism (SNPs), and copy number variations (CNVs) ( Chen et al, 2019 ; Zhang C. et al, 2019 ; He et al, 2021 ; Liu et al, 2021a ). However, most of these studies focused on the genetic variations and forensic features of low-density genetic markers in the Han Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic distances between the Manchus and the Altaic language-speaking populations such as Hezhen, Daur, and Oroqen were smaller than those of other language-speaking populations ( Zhao et al, 2011 ; Liu et al, 2013 ; Xing et al, 2019 ). Most genetic investigations based on the high-density genome-wide genetic variations from non-Altaic people in East Asia have revealed a fine-scale genetic landscape of genetic diversity and population admixture among the populations from different-language families ( He et al, 2021a , c ; Liu et al, 2021a , b ; Wang et al, 2021d ; Yao et al, 2021 ). Besides, recent genome-wide studies among Altaic-speaking populations in Northeast Asia have also found differentiated genetic admixture profiles between northern and southern Altaic-speaking populations and eastern and western Mongolians ( He et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%